Study of Workplace Radiation Dose Rate during the Brain Scanning Procedures - Ahasan, MM; Badruddoza, SM; Paul, AK; Dey, SK; Ahmed, FU (TAJ: Journal of Teachers Association, 2009)
Radiation dose rate in the gamma camera workplace were measured during brain scanning procedures using a dose of 15-20 mCi99mTc-pertechnetate (99mTcO4-) given intravenously to each patient. The study based on randomly selected 20 patients duly registered for brain scan at Centre for Nuclear Medicine & Ultrasound (CNMU), Rajshahi. Radiation dose rate at the patienthandling place and computer-operating place were measured by a high sensitive portable dose ratemeter and a NaI detector. Brain imaging procedures were usually done two hours post injection. Radiation dose rate at the patient-handling place found to be 20±4μSvhr-1 and the computer-operating place were 2±0.4μSvhr-1. Patient skull surface doses were measured also and found to be 120±24μSvhr-1 (one hour post injection) and 80±13μSvhr-1 (two hours post injection). The results showed that the radiation dose rate in the gamma camera workplace during brain scanning procedures found to be nearly 6 to 60 times higher than the background level. The research goals of the study were to measure the workplace radiation level during brain scanning procedures and sketched some special remedial measures to reduce the radiation exposure rate in the gamma camera work environment. doi: 10.3329/taj.v17i1.3486 TAJ 2004; 17(1) : 27-30